Help-seeking trajectory in patients with rheumatoid arthritis - Pelaez, Ingris (Clin Rheumatol, 2015)
Early diagnosis and treatment of rheumatoid arthritis (RA) depends on the degree of fit between the characteristics of the patients and those of the health services. Ensuring timely assessment and treatment is the ideal medical care of RA. The reasons that underlay delays and the help-seeking trajectories are contextually determined. This study aims to identify the empirical evidence related to the help-seeking process and delay in RA in Latin America and to create a comprehensive model integrating the RA medical care processes of help-seeking and delay in a mixed health care system with variable accessibility. Non-systematic literature review of studies with both quantitative and qualitative methodology was conducted. Most of the research about delay and its associated variables have been undertaken in European countries and with White population and cannot be translated to the Latin America context where this research is almost inexistent. These countries have a completely different social context, and for most of the population, the health services are insufficient, inaccessible, fragmented, limited, and inequitable. Our results also show that in RA medical care utilization research, the theories and measurements of the constructs of illness trajectories, help-seeking, and accessibility are not integrated. We offer a conceptual framework that integrates help-seeking trajectories, delay, and accessibility of RA medical health services. If research on RA service utilization is to be undertaken in these countries, there is a need for a comprehensive framework than can enable researchers to integrate and contextualize the study of the problems within broad theoretical and methodological perspectives.